THE COST OF A TRANSFORMER AND THE IMPORTANCE OF ITS HEATING - Sorimsokov Uchkun Soatboy o’g’li ,Boliyev Alisher Mardiyevich, Suyarov Anvar Olim o’g’li; Nurullayev O.U. (Zeta Repository, 2023)
The problem of transformer losses and their causes are studied and recommendations for their optimal values are given. Transformer heating and cooling methods are studied.